Teaching-learning strategies in initial education - Author; Author (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The Ecuadorian Constitution recognizes education as a public function of the first order due to the impact it represents for the development of the country, therefore guaranteeing its continuity, quality and constitutes a priority task for the State. In Ecuador, the implementation of playful methods has been provided as basic tools, where the kindergarten teacher prepares to teach their students using tools capable of motivating interest in study and that children develop their skills and psychomotor abilities. The game as a tool influences the socio-affective development of the child, art allows to interpret and design their own experiences, facilitating that the teacher can know the infant in terms of thought, feelings, and interpretation. The objective of the work is to offer the results of an analysis on the need to deepen the methods required to guarantee a preschool education capable of motivating the desire to learn in preschoolers. For this, the inductive method was used, which allowed, from the analysis of the general situation of pedagogical methods in initial teaching, to reach precise conclusions on the subject studied. Desk research was put into practice for the review and analysis of the bibliographies associated with the topic. The work allowed to reveal the relevance of the pedagogical methods during the exercise of the initial teaching.